Usborne Timelines of World History - Chisholm, Jane; Designed by Newell, Keith [et al.] ; History Consultant Millard, Anne Dr. (London Usborne, 2000)
An astonishingly thorough reference book covering the most important dates in world history from 9000 BC right up to the present day. Densely illustrated , including maps, photographs and diagrams, this invaluable book will be a handy and essential reference tool for students throughout secondary school.
Includes Index and Colored Illustrations.
Keywords: World History -- Chronology, Historical